2022-RA-853-ESGO Analysis of the gender distribution among the invited speakers at European society of gynaecological oncology (ESGO) biannual congresses 2017, 2019, and 2021. (20th October 2022) - Bilir, Esra; Kacperczyk-Bartnik, Joanna; Razumova, Zoia; Nasser, Sara; Strojna, Alexandra; Nikolova, Tanja; Pletnev, Andrei; Zalewskii, Kamil; Bizzarri, Nicolò; Morice, Philippe; Mirza, Mansoor Raza; Fagotti, Anna; et al.
Abstract : Introduction/Background: The representation of female leadership acrossdifferent medical specialities does not reach parity. It is even more evidentin surgical specialities like gynaecological oncology. The primary aim of thisstudy was to analyse gender distribution of invited speakers during ESGOCongresses. Methodology: In this cross-sectional study, we analysed data fromESGO Congresses in 2017, 2019, and 2021.We identified gender of chairpersons &presenters (together they represent the invited congress faculty) according tothe given full name in the congress program. We used Google search when wecould not identify gender according to the given name. We analysed the databased on gender of chairpersons, presenters, and female-to-male ratios insessions. We excluded 'glass with an expert' talks and ceremonial sessions, such as opening and closing ceremonies. As a subgroup, we investigated genderdistribution in sessions of the European Network of Young GynaecologicOncologists (ENYGO). Results: In the pooled analysis of all 3 congresses, weidentified a total of 516 chairpersons/speakers with a female to male ratio of0.66. In 2017 female faculty contribution was 30%, in 2019 41% and in 2021 31%.In the pooled analysis, scientific programmecommittees consisted of 65% male and 35% members. The female contribution toscientific programme committee was stable among the 3 analysed congresses. In 2017 and 2021 the scientific programmecommittee was chaired by a man, respectively, in 2019 by a female. In all 3 congresses there was a substantially highernumber of pure male sessions (chairs & presenters are male only) than pure femalesessions. The number of pure male sessions decreased over time in the 3analysed congresses. Conclusion: ESGO has implemented the general rule of genderbalance into ESGO congress Standard Operating Procedures (SOPs) in 2020, inaddition to country balance and interdisciplinary approach. Based on ouranalysis, ESGO congresses have an acknowledgeable-level of gender balance. Amore comprehensive analysis with more details will be provide at the ESGOcongress in Berlin.